Human Resource Management in an Organization - Alfian, Alfian; Amrin, Amrin; Darwis, Darwis; Farida, Umi; Yusriadi, Yusriadi (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 1 No 1 (2020): 1st International Conference on Engineering, Technology, and Social Sciences (ICONETOS)DO - 10.18860/iconetos.v1i1.1158, 2020)
Human resource management is organizing, implementing, and controlling human resources within the organization to achieve goals effectively and efficiently. Human resources, as one of the funds in the organization, play an essential role in the success of achieving organizational goals. Success depends on the ability of human resources to carry out their duties and functions. Employee performance is the result of the quality and quantity of work achieved by an employee in carrying out tasks following the responsibilities given to him. Productivity is servicing union input resources used in the production process. Motivation is a collection of behaviors that provide a foundation for someone to act in a way that directed to a specific goal. Seven crucial factors that are used to employee performance Work spirit is a condition of how an employee does the work every day. The higher the mind, the work will improve employee productivity.